2013
DOI: 10.4103/2230-8210.119618
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of adiponectin level in obese and lean Nepalese population and its possible correlation with lipid profile: A cross-sectional study

Abstract: Objective:Adiponectin- one of the most important adipokines plays a pivotal role in carbohydrate and lipid metabolism and vascular biology. Changing food trend and lifestyle has tremendously affected the health status of Nepalese population. Studies have shown that between 1996 and 2006 obesity in Nepal has increased from 1.6% to 10%. Studies have been conducted in Nepal on the prevalence of obesity and its correlation with lipid profile. But based on our knowledge, this is the first study correlating adiponec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
2
9
0
1
Order By: Relevance
“…In agreement with these findings, Tamang et al, [29] reported that serum adiponectin correlates positively with HDL-C levels in obese subjects. They suggested that the possible mechanisms may partially be explained with the activated receptor, which affects the genes, associated with HDL metabolism.…”
Section: Discussionsupporting
confidence: 63%
“…In agreement with these findings, Tamang et al, [29] reported that serum adiponectin correlates positively with HDL-C levels in obese subjects. They suggested that the possible mechanisms may partially be explained with the activated receptor, which affects the genes, associated with HDL metabolism.…”
Section: Discussionsupporting
confidence: 63%
“…Another possible mechanism is that HDL cholesterol correlates negatively with ANG II, but ANG II is positively associated with VEGF in TNBC, while the VEGF signaling pathway plays a pivotal role in TNBC (2, 32, 33); therefore, low HDL may lead to more aggressive behavior of TNBC. Besides that, a positive correlation was found between adiponectin and HDL (34, 35), and in a Korean cohort study, serum adiponectin concentrations showed a significant inverse association with ER/PR-negative BC recurrence (p = 0.009) (9). These are just assumptions regarding the underlying mechanisms for the influence of HDL on TNBCs, however, and this is still far from explaining why low HDL acts differently between TNBC and non-TNBC patients.…”
Section: Discussionmentioning
confidence: 90%
“…[46] In agreement with our study, no correlation was found between parameters of fatness and adiponectin level. [46] An inverse correlation was also found between adiponectin, TC and TG by Tamang et al [47] Another study revealed a significant negative correlation between adiponectin and weight, BMI, fat mass, adverse lipid levels like TC and TG and a positive correlation with serum HDL levels. [9] The study consisted of a small sample size of patients with more pronounced obesity.…”
Section: Discussionmentioning
confidence: 94%